2007
DOI: 10.1002/hup.832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking marijuana on focal attention and brain blood flow

Abstract: Using an attention task to control cognitive state, we previously found that smoking marijuana changes regional cerebral blood flow (rCBF). The present study measured rCBF during tasks requiring attention to left and right ears in different conditions. Twelve occasional marijuana users (mean age 23.5 years) were imaged with PET using [15O]water after smoking marijuana or placebo cigarettes as they performed a reaction time (RT) baseline task, and a dichotic listening task with attend-right- and attend-left-ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…The most frequent finding was the increased resting prefrontal, insular and anterior cingulate activity (Volkow et al 1996 ;Mathew et al 1997Mathew et al , 1998Mathew et al , 1999Mathew et al , 2002. Studies that combined the administration of THC or marijuana with a cognitive task also described modulated activation in these regions (O'Leary et al 2002(O'Leary et al , 2003(O'Leary et al , 2007Borgwardt et al 2008 ;Phan et al 2008 ;Fusar-Poli et al 2009). The acute administration of CBD has been associated with increased resting activity in the left parahippocampus gyrus and a reduction in medial temporal cortex activity while subjects were processing intensely fearful faces (Crippa et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent finding was the increased resting prefrontal, insular and anterior cingulate activity (Volkow et al 1996 ;Mathew et al 1997Mathew et al , 1998Mathew et al , 1999Mathew et al , 2002. Studies that combined the administration of THC or marijuana with a cognitive task also described modulated activation in these regions (O'Leary et al 2002(O'Leary et al , 2003(O'Leary et al , 2007Borgwardt et al 2008 ;Phan et al 2008 ;Fusar-Poli et al 2009). The acute administration of CBD has been associated with increased resting activity in the left parahippocampus gyrus and a reduction in medial temporal cortex activity while subjects were processing intensely fearful faces (Crippa et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana with THC use was associated with increased rCBF (relative to a cigarette containing marijuana with the THC removed) in the left ventral frontal cortex, right insula, bilateral temporal pole, ACC, temporal and cerebellar cortices, whereas there was decreased activity in the left superior temporal gyrus (O'Leary et al 2002). In a subsequent study by the same group, 12 recreational cannabis users were tested (O'Leary et al 2007). rCBF was measured during a tasks requiring attention to left and right ears in different conditions, after smoking marijuana cigarettes with or without THC, at least a week apart using a double-blind design.…”
Section: Acute Effects Of Cannabis On Activation During Cognitive Tasksmentioning
confidence: 99%
“…O'Leary et al demonstrated substantial reduction in blood flow to the temporal lobe when volunteers showed impaired performance of auditory attention tasks [21]. Marijuana smoking has also been shown to increase blood flow in the frontal lobes and lateral cerebellum at rest [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired performance on sustained attention (eg. on continuous performance tasks), selective, focused and divided attention tasks, as well as in preattentive sensory memory have been demonstrated after acute administration of cannabis or THC to humans (Ilan et al, 2004;O'Leary et al, 2007;Hunault et al, 2009;Ramaekers et al, 2009). Accuracy, increased error rates and slowed reaction times were shown in some studies to be dose-related.…”
Section: Nadia Solowij and Nicole Pesamentioning
confidence: 99%
“…Regular but infrequent cannabis users showed dose-dependently impaired performance (greater errors) on a Sternberg memory task following acute administration of THC (O'Leary et al, 2007), and these have been associated with reduced frontal-midline EEG theta power (Bocker et al, 2007). Acute effects of cannabinoids on electrophysiology have also been demonstrated in infrequent cannabis users for the mismatch negativity (MMN) component of the ERP (MMN being an index of preattentive sensory memory) (Juckel et al, 2007) and the P300 component (an index of the allocation of attentional resources and updating of memory traces) (Roser et al, 2008).…”
Section: Short-term Effects In Humansmentioning
confidence: 99%